2016
DOI: 10.1063/1.4945614
|View full text |Cite
|
Sign up to set email alerts
|

Examination of ionic wind and cathode sheath effects in a E-field premixed flame with ion density measurements

Abstract: The effect of the ionic wind on a premixed methane-air flame under a DC electric field is studied via mapping of the ion density with Langmuir probes. Ion densities were observed to increase near the burner with increasing electrode voltage up to 6 kV. Past this electrode supply voltage, ion densities ceased increasing and began to decline in some locations within the premixed flame. The increased ion density is caused by an increase in ionic wind force and cathode sheath thickness. The plateau in density is d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…At high enough voltages, all ions produced in the flame front are attracted to the cathode and collected, thereby preventing further increase in current flux. Jacobs and Xu confirmed this behavior with ion density measurements inside a quasi-onedimensional flame under a dc electric field [30]. They found that the increase in ion density plateaued at 6 kV, and further increase in voltage caused no change in the ion density and current.…”
Section: A Electrical Characteristicsmentioning
confidence: 67%
See 3 more Smart Citations
“…At high enough voltages, all ions produced in the flame front are attracted to the cathode and collected, thereby preventing further increase in current flux. Jacobs and Xu confirmed this behavior with ion density measurements inside a quasi-onedimensional flame under a dc electric field [30]. They found that the increase in ion density plateaued at 6 kV, and further increase in voltage caused no change in the ion density and current.…”
Section: A Electrical Characteristicsmentioning
confidence: 67%
“…The small and medium anodes all have exponential current profiles, which indicate an asymptotic upper limit on the current, which means an upper limit on the effect of the electric field on the flame, without gas breakdown. The cause for this upper limit is usually current saturation of the cathode as seen and described by other works [16,[29][30][31][32]. At high enough voltages, all ions produced in the flame front are attracted to the cathode and collected, thereby preventing further increase in current flux.…”
Section: A Electrical Characteristicsmentioning
confidence: 93%
See 2 more Smart Citations
“…The Langmuir probe, which was made of carbon steel, was a plate to plate type with a diameter of 4 mm and a spacing of 5 mm for the measuring head, and the rest part of the probe was covered with PTFE. The power supply for the Langmuir probe was 400 V, which was in the linear voltage-current region [32], and series resistance was 150 kΩ.…”
Section: Experimental Apparatusmentioning
confidence: 99%